2018
DOI: 10.25186/cs.v13i2.1419
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION OF BEVERAGE QUALITY IN Coffea canephora Pierre ex A. Froehner

Abstract: Differentiation of coffee according to its quality can result in added value. Both the coffee genotype and the environment influence beverage quality. The main species grown in the Amazon region is C. canephora, which includes two distinct botanical varieties: Conilon and Robusta. The aim of this study was to characterize beverage quality in C. canephora and distinguish the Conilon and Robusta botanical varieties and intervarietal hybrids. We evaluated the beverage quality of 130 superior clones from samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 8 publications
0
25
1
2
Order By: Relevance
“…Estimates of heritability (h 2 ) and of the experimental coefficient of variation (CV e ) indicated that the post-harvest procedures were adequate in the evaluated environments. Higher estimates of the coefficient of variation were observed by (Souza et al, 2018a) in the evaluation of 130 C. canephora accessions in a single environment.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Estimates of heritability (h 2 ) and of the experimental coefficient of variation (CV e ) indicated that the post-harvest procedures were adequate in the evaluated environments. Higher estimates of the coefficient of variation were observed by (Souza et al, 2018a) in the evaluation of 130 C. canephora accessions in a single environment.…”
Section: Resultsmentioning
confidence: 83%
“…For field experiments, estimates of the coefficient of variation lower than 10% can be considered low (Pimentel-Gomes, 2009) (Table 4). In evaluation of a greater number of clones, Souza et al (2018a) observed an estimate of the coefficient of variation of 13.26 in evaluation of the attributes of beverage quality of 130 genotypes of C. canephora in a single environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a long time, C. canephora beans were used only for blends with arabica coffee beans. However, more recently, the beverage quality of the beans from this coffee tree has been appreciated for aroma and flavor traits: less sweetness, less acidity, and greater bitterness (Souza et al 2018). According to the Fine Robusta protocol, the main organoleptic attributes for evaluation of the Canephora species are aroma, flavor, aftertaste, salt/acidity ratio, bitterness/sweetness ratio, mouth-feel, cup balance, uniformity, cleanness, and overall aspects.…”
Section: Beverage Qualitymentioning
confidence: 99%